Biostability of polyester fabric modified by silver nanosuspension - Kisterska, L.D.; Loginova, O.B.; Kondratiuk, T.O.; Beregova, T.V.; Boshitska, N.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
The possibility of using silver nanoparticles (NAg), obtained by the innovative ion-plasma technology proved to provide biocidal protection for textile materials. Substance of NAg in the presence of microorganisms was investigated on the surface of a waterproof polyester fabric with polyurethane impregnation by the methods of scanning electron microscopy and X-ray spectral microanalysis. The bactericidal effect of the “Ag Nanofluid” nanosuspension is shown for test cultures of bac teria Pseudomonas aeruginosa, Staphylococcus aureus Escherichia coli, as well as the fungistatic effect for the yeast Candida Albicans, a significant increase in the biostability is proved for the studied tissue treated “Ag Nanofluid”. Under the action of NAg these test cultures of bacteria and yeasts undergo significant morphological changes (deformations, surface damage and cell integrity), test cell cultures of microorganisms under these conditions selectively accumulate certain chemical elements, which leads to their destruction.